A cross sectional study of trihexyphenidyl utilization on patient receiving antipsychotic therapy - Addiniya Nurul Azmi; Sufi Desrini (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: Psychotic disorder becomes a mental health problem recently that reduce quality of life of the patient. As the matter of fact, psychotic treatment induce another problem such as extrapyramidal symtomps (EPS). Trihexyphenidyl is the first choice as conjuctive treatment to prevent EPS. Objective: To determine the description and characteristics of trihexyphenidyl utilization on patient with psychotic who receive antipsychotic therapy at Ghrasia Hospital Yogyakarta. Methods: This study is a non-experimental descriptive with cross sectional design with the secondary data obtained from the medical record of patients with psychotics on January 2014 – January 2015 to perceive the utilization of trihexyphenidyl on patient who receive antipsychotic therapy at Ghrasia hospital. The sample is determined by Slovin formula, the data is analyzed with univariat analysis technic. Results: The majority of psychotic patients at the Ghrasia Hospital are about 25-40 years old (61,7%). It describes that the pattern of the psychotic disorder most likely happening at middle age, which 98 patients are male (63,6%). The combination of two antipsychotics becomes the most used regiment at Grhasia, 113 patients (73,4%) receive the combination of two antipsychotics theraphy, 39 patients (25,3%) receive single antipsychotic therapy and 2 patients (1,3%) receive the combination of three antipsychotics. 136 patients (88,3%) receive trihexyphenidyl twice a day on undefined skizophrenia 65 patients (42,2%) and 18 patients (11,7%) once a day. 149 patiens (96,8) are not examined before THP is given before the initiaton of the theraphy. Conclusion: Administration trihexiphenidyl as adjunctive therapy is given to the psychotic patients twice a day and most of them are not initiated by the examination of syndrome extrapyramidal.